Digital Natives at Risk: Exploring Adolescents’ Engagement in Risky Online Activities in Makassar - Adityar, Adityar; Muhammad Iqbal Sultan (Al-MUNZIR, 2025)
As a generation of digital natives, adolescents have integrated the internet as an inseparable part of their daily lives. While it offers various new opportunities, internet use also presents numerous risks. This study examines risky online behaviors among high school students in Makassar City using a quantitative approach and survey method involving 153 respondents selected through accidental sampling. Data collection focused on four categories of risky behavior: misuse of personal data, exposure to pornographic content, threats to personal safety, and cyberbullying. The data were analyzed using McLuhan’s Media Ecology Theory framework. The findings reveal that a majority of respondents had shared sensitive personal information, such as their school name (74.5%), phone number (45.8%), and home address (32.7%), thereby increasing the risk of privacy violations and data misuse. Exposure to pornographic content was notably high, with 82.4% accessing it unintentionally and 38.6% intentionally. Furthermore, 50.3% reported having received and 19% having distributed sexually explicit content. Personal safety risks were also significant, with 73.9% having interacted with strangers online, 33.3% having sent personal photographs, and 49.7% admitting to in-person meetings following online communication. Cyberbullying emerged as a prominent issue, both in terms of victimization and perpetration, with 62.1% having received humiliating comments and 12.4% having received threats, while 54.2% admitted to sending insulting messages and 7.3% to issuing threats. This study contributes to the discourse on youth engagement with digital media by providing empirical insights into patterns of risky behavior online.